Reduced tillage and subsurface fertigation improve productivity and economic benefits in the cotton-wheat cropping system - Singh, Kulvir; Singh, Manpreet; Mishra, Sudhir Kumar; Soufan, Walid; Habib-ur-Rahman, Muhammad; El Sabagh, Ayman (Frontiers in Sustainable Food Systems, 2023)
Soil compaction under repetitive tillage and surface flood method of irrigation (SFMI) are major hurdles for sustaining crop production in India, necessitating adoption of efficient soil and water management strategies. Hence, a 3 yr field study was conducted at two diverse agro-climatic locations (Abohar and Faridkot) to investigate the impact of subsurface drip (SUSD) fertigation on crop and water productivity of cotton-wheat cropping system (CWCS), over Traditional Practice-TP (conventional tillage with SFMI and manual application of nutrients). The experiment was conducted in a Factorial randomized complete block design with 3 levels of subsurface drip irrigation-SUSDI 100, 80 and 60% of crop evapo-transpiration (ETc) and 2 fertigation levels 75% recommended dose of nutrients (RDN) and 100% RDN, while TP (Control 1) and surface drip (SD) fertigation at 80% ETc coupled with 100% RDN (Control 2), served as two control treatments. Cotton was raised through reduced tillage, while zero till drill was used for sowing wheat. Results revealed that barring SUSDI at 60% ETc, both crops exhibited improved yield under all drip combinations of reduced/zero tillage over TP. Better mass and higher length of cotton roots in drip fertigation was evident due to improved steady state infiltration rate (SSIR) and reduced bulk density (BD) under conservation tillage. When 100% RDN was applied, SUSDI's of 100 and 80% ETc resulted in 26.7 and 24.7% higher seed cotton yield (SCY) than TP. Similarly, wheat yield with 100% RDN was improved by 10.5% and 14.4% under SUSDI's of 80% and 100% ETc, respectively over the TP. Results envisage that SUSD can be clubbed with reduced tillage for better soil health, improved crop yield and higher apparent water productivity. Improved benefit: cost (B: C) owing to enhanced monetary returns over TP also substantiated that reduced tillage with SUSD is viable and remunerative practice for CWCS.Font: 14 pt Formatted[ayman elsabagh]: Font: 10.5 pt Formatted[ayman elsabagh]:2 lowering BD and improving SSIR, while SUSD could save huge irrigation water besides enhanced input use efficiency leading to higher crop productivity.